Emergency thermal energy storage: cost & energy analysis - Bembry, Walter T., IV (Kansas State University, 2011)
The need to store and access electronic information is growing on a daily basis as more and more people conduct business and personal affairs through email and the internet. To meet these demands, high energy density data centers have sprung up across the United States and around world. To ensure that vital data centers run constantly, proper cooling must be maintained to prevent overheating and possible server damage from occurring. Emergency cooling systems for such systems typically utilize traditional batteries, backup generator, or a combination thereof. The electrical backup provides enough power to support cooling for essential components within the data centers. While this method has shown to be reliable and effective, there are several other methods that provide reliable emergency cooling at a fraction of the cost. This paper address the lack of information regarding the initial, operation, and maintenance costs of using Thermal Energy Storage (TES) tanks for emergency cooling. From research and various field examples, five emergency cooling system layouts were designed for various peak cooling loads. Looking at the different cooling loads, components, and system operations an economic evaluation of the system over a 20 year period was conducted. The economic analysis included the initial and maintenance costs of each system. In an effort to better understand power consumption of such systems and to help designer’s better estimate the long term costs of TES tanks systems, five layouts were simulated through a program called TRNSYS developed for thermal systems. To compare against current systems in place, a benefit to cost ratio was done to analyze TES versus a comparable UPS. The five simulated systems were one parallel pressurized tank, one parallel and one series atmospheric tank, one parallel low temperature chilled water, and one series ice storage tank. From the analysis, the ice storage and pressurized systems were the most cost effective for 1 MW peak cooling loads. For 5 MW peak cooling loads the ice storage and chilled water systems were the most cost effective. For 15 MW peak loads the chilled water atmospheric TES tanks were the most cost effective. From the simulations we concluded that the pressurized and atmospheric systems consumed the least amount of power over a 24 hour period during a discharge and recharge cycle of the TES tank. From the TRNSYS simulations, the ice storage system consumed 22 – 25% more energy than a comparable chilled water system, while the low temperature storage system consumed 6 – 8% more energy than the chilled water system. From the benefit-cost-ratio analysis, it was observed that all systems were more cost effective than a traditional battery UPS system of comparable size. For the smaller systems at 1 MW the benefit-cost-ratio ranged between 0.25 to 0.55, while for larger systems (15 MW) the ratio was between 1.0 to 3.5 making TES tanks a feasible option for providing emergency cooling for large and small systems.
Keywords: Emergency cooling thermal energy storage tanks; Mechanical Engineering (0548)